Potential of Microbial Polysaccharides as Halal Food Hydrocolloids / Assoc. Prof. Dr. Shuhaimi Mustafa, Dzulkifly Mat Hashim and Nurul Hawa Ahmad - Mustafa, Shuhaimi; Mat Hashim, Dzulkifly; Ahmad, Nurul Hawa (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
While the end-use markets for gelatin is largely comprised of food and beverage companies, the global market for gelatin is anticipated to reach 357.8 thousands metric tons by 2015 driven by increasing demand from developing countries. The most ubiquitous source for commercial gelatin is limited to pig skins or cow skins and bones. However animal-based gelatin is restricted due to religious and health concerns. Alternatively, microbial polysaccharides have great potential as viscosifying, stabilizing, emulsifying or gelling agents in food and pharmaceutical products. Gellan gum and dextran are microbial polysaccharides synthesized by Sphingomonas elodea and Leuconostoc mesenteroides respectively. The rheological properties of gellan/dextran blends were investigated as compared to porcine and bovine gelatin. Rheological properties of hydrocolloids are very important for applications of food products particularly in food product development and process design. The blends exhibited shear thinning behaviour and a blend of equal proportion (1:1) revealed a distinct gel point (G'=G") while further addition of dextran in the blend (1:2 ,1:3) resulted predominating liquid like behaviour (G'>G").The blend rheology would help to understand interactions between two hydrocolloids and to design food products with desired textural attributes.